Kebijakan pendidikan : Kebijakan pendidikan terhadap kesenjangan apresiasi guru - Fitriyah, Ana Nur (Maliki Interdisciplinary Journal, 2024)
This article discusses education policies that aim to reduce the gap in teacher appreciation in Indonesia. Although teachers play an important role in the education process, there is still inequality in the rewards and recognition they receive. This article analyzes the various policies that have been implemented by the government to improve teacher appreciation, including salary increases, training programs and merit awards. It also evaluates the effectiveness of these policies and identifies challenges that remain in their implementation. Using a qualitative approach, the study highlights the importance of continuous and comprehensive support to ensure teachers' welfare and motivation in carrying out their duties. The article concludes that despite some progress, further efforts are needed to achieve comprehensive appreciation equality for all teachers in Indonesia.